Pengaruh Modal Intelektual dan Peluang Pertumbuhan Perusahaan terhadap Initial return: Bukti pada Perusahaan yang Melakukan IPO Periode 2020-2022 - Widodo, Condro; Wijaya, R. Muh Syah Arief Atmaja; Budiman, Arief; Vendy, Vicky; Sucahyati, Diarany (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the effect of intellectual capital and company growth opportunities on the initial return of IPOs for the 2020-2022 period. This period was used because during that period there was a pandemic due to the corona virus. The research population is all companies that carried out initial stock offerings (IPO) in Indonesia during the 2020-2022 period. This research uses a purposive sampling technique to determine the research sample. The results of this research found that a company's intellectual capital has no effect on initial returns, meaning that this research does not support the resource-based theory. However, on the other hand, the results of this research show that company growth opportunities have a positive effect on initial returns, meaning that the results of this research also support signaling theory.